Taxonomic treatment of the tribe Boldoeae (Nyctaginaceae) - Hernández Ledesma, Patricia (Instituto de Ecología, A.C., 2021)
Background and Aims: The tribe Boldoeae (Nyctaginaceae) is distributed from Mexico to northern South America. Throughout its taxonomic history there has been debate regarding the circumscription of the included genera, either recognizing Salpianthus in a broad sense, or accepting Boldoa and Cryptocarpus as separate. The tribe is characterized by plants with achenes surrounded by the persistent base of the perianth, but not fused to it, a rare characteristic within the family. The objective of this work is to present an updated treatment of the tribe, to analyze the generic boundaries and to provide identification keys and descriptions of their genera and species. Methods: A bibliographic review of taxonomic studies and protologues of Boldoeae was carried out, herbarium specimens, including types, were observed, and online collections and specialized internet portals were consulted in order to update the taxonomic information of the tribe and to generate distribution maps. Key results: The tribe Boldoeae includes three genera and six species, all of them present in Mexico. Boldoa and Cryptocarpus, that are monotypic, are found to the north of South America, but the latter with disjunct distribution, while Salpianthus, with four species, is endemic to Mexico. Characteristics of the inflorescences and the perianth have sufficient taxonomic relevance to consider the three genera as separate. Conclusions: Boldoeae is made up of Boldoa, Cryptocarpus and Salpianthus. Although the debate within this has focused on the generic circumscription, it seems that the delimitation between the Salpianthus species is more relevant, especially in the little-collected species such as S. aequalis or the one known only from the type specimens, S. standleyi, which does not allow to know its morphological variation and properly compare them.